Whole-genome resequencing reveals genetic diversity, differentiation, and selection signatures of yak breeds/populations in southwestern China - Zhang, Shilin; Li, Jing; Zhao, Yanhua; Tang, Yujun; Li, Hao; Song, Tianzeng; An, Tianwu; Guan, Jiuqiang; Li, Xiaowei; Zhang, Ming (Frontiers in Genetics, 2024)
The Sichuan-Yunnan region is the main production area of yaks in southwestern China, with rich genetic resources of Yaks. Nevertheless, there have been limited study on the genetic characteristics of the entire yak populations in Tibet and southwestern China. In this study, we performed whole-genome resequencing to identify genetic variation information in a total of 198 individuals from six yak breeds (populations) in Sichuan (Muli yak, Jinchuan yak, Changtai yak, Maiwa yak), Yunnan (Zhongdian yak), and Tibet (Tibetan yak). The aim was to investigate the whole-genome genetic diversity, population genetic structure, and genome selection signatures.We observed that all six populations exhibit abundant genetic diversity. Except for Tibetan yaks, which showed low nucleotide diversity (0.00104), the remaining yak populations generally displayed high nucleotide diversity (0.00129 ~0.00153). Population genetic structure analysis revealed that, among the six yak populations, Muli yak exhibited greater differentiation from other yak populations and formed a distinct cluster independently. The Maiwa yak population displayed a complex genetic structure and exhibited gene exchange with Jinchuan and Changtai yaks.Positive selection signals were detected in candidate genes associated with growth (GNB4, HMGA2, TRPS1, and LTBP1), reproduction (PI4KB, DYNC1I1, and GRIP1), immunity (CD200 and IL1RAP), lactation (SNX13 and CPM), hypoxia adaptation (NDUFB6, PRKN, and MRPS9), hair (KRT24, KRT25, and KRT26), meat quality (SUCLG2), digestion and absorption (CLDN1), and pigment deposition (OCA2) using the integrated Pi and FST methods. This study provides significant insights into understanding the whole-genome genetic characteristics of yak populations in Tibet and southwestern China.